P143 Outcomes of ulcerative colitis-associated dysplasia patients treated with endoscopic submucosal dissection: An extended analysis of a single center cohort. (30th January 2023) - Park, S; Hong, S W; Hwang, S W; Park, S H; Ye, B D; Byeon, J S; Myung, S J; Yang, S K; Yang, D H
Abstract: Background: Total proctocolectomy has been recommended for patients with ulcerative colitis (UC)-associated dysplasia due to the risk of its progression to colorectal cancer or metachronous recurrence. Recently, endoscopic resection has been considered as a therapeutic option for dysplasia in UC, and endoscopic submucosal dissection (ESD) has been recommended for lesions where endoscopic mucosal resection is unsuitable. We aimed to investigate the long-term outcomes of UC patients who underwent ESD for dysplasia or early colorectal cancer Methods: We retrospectively reviewed 47 patients with UC-associated dysplasia/cancer referred for potential ESD to treat non-polypoid or sessile dysplasia between August 2009 and August 2022 at Asan Medical Center, a tertiary hospital in Seoul. Indications for ESD were determined according to the criteria applied for sporadic colorectal neoplasms based on magnifying endoscopy. Results: The median age at UC diagnosis was 45 years, and 24 patients (51%) were male. The median duration of UC was 13 years. Colectomy was recommended for 11 patients, and the remaining 36 patients underwent ESD. The en bloc resection rate was 88.9% (32/36), and the histologic complete resection rate was 77.8% (28/36). Five patients underwent colectomy after ESD due to missed adenocarcinoma, deep submucosal cancer, and multiple dysplasia. A total of 31 patients were followed-up after ESD. Their mean (standard deviation) follow-up period was 45.9 (±30.6) months, and the mean number of post-ESD surveillance endoscopies was 3 (±2). Local recurrence of dysplasia occurred in 3 (3/31, 9.6%) patients; metachronous recurrence occurred in 7 patients (7/31, 22.6%). There were no cases of metachronous colorectal cancer. Conclusion: ESD for discrete dysplastic lesions in UC patients is feasible and shows favorable outcomes in terms of colorectal cancer prevention. However, surveillance colonoscopy with short intervals is warranted due to the high metachronous recurrence rate.